Microparticles of Diethylcarbamazine Citrate for the Treatment of Lymphatic Filariasis - Shukla*, Rahul; Kumar, J.; Dwivedi, P.; Gatla, P.; Mishra, P.R. (Asian Journal of Chemistry, 2013)
The aim of the study is to study the fabrication of microparticles for antifilarial drug diethylcarbamazine citrate with increased efficacy, decrease dose and minimise its side effects. Lymphatic filariasis is one of the major causes of chronic disability in the developing countries and, as such, produces a considerable economic burden. The microparticles were prepared by two steps, using alginates by spray-drying step and crosslinking step. Entrapment efficiency, in vitro drug release study was performed of the developed formulations. FT-IR and mass spectrophotometry were performed of the formulations. Diethylcarbamazine citrate is drug used in the management of lymphatic filariasis in both early and advanced stages. In the development of alginate/chitosan microparticles for the diethylcarbamazine citrate delivery to lymphatic system, the preformulations studies were performed. Microparticles polymer network and, consequently, drug loading level and release, were affected by the alginate and crosslinking agent concentrations. Results were favourable for our novel drug delivery system developed for neglected tropical disease such as filariasis.